DESAIN LANSEKAP SEAMEO BOGOR SEBAGAI KAWASAN AGROEDUWISATA - Rachmanto, Eurico Pratama; Hadi, Akhmad Arifin (Jurnal Kreatif : Desain Produk Industri dan Arsitektur, 2024)
SEAMEO (Southeast Asian Ministers of Education Organization) BIOTROP is a center for the study of tropical biology under the coordination of the Ministry of Education, Culture, Research and Technology. Its activities include research, training, networking, and personnel exchange and information dissemination in tropical biology. More than 5000 visitors per year take advantage of the facilities and resources available at BIOTROP. To maximize this potential, BIOTROP has launched an Agro-Edu-Tourism program. The concept of Agro-Edu-Tourism was chosen because the main activities at BIOTROP are research in the field of tropical biology and agriculture in a broad sense, as well as tourism activities are considered as one of the most developing industries in the world. The aim of this research is to design the BIOTROP landscape that can be used as a facility for agroedutourism and enhance ecosystem services. The basic concept of this design is to maximizes the functions of the existing BIOTROP area, which currently serves as a tourist destination with a foundation in agriculture and education. The proposed basic concept is "Familiarizing oneself with Agriculture", where visitors are invited to get closer to agricultural products, engage in recreational activities in agricultural areas, and experience firsthand farming activities such as land cultivation, planting, caring for crops, and harvesting. Additionally, this research contains a series of designs consisting of project acceptance, analysis, conceptual studies, schematic designs, site plan, and construction drawings. The final results of this research are recommendation concept, site plan, detailed drawings, and design illustrations.